A novel MEN1 intronic mutation associated with multiple endocrine neoplasia type 1. - Lemos, M; Harding, B; Shalet, S; Thakker, R (2007)
OBJECTIVE: To investigate a family with an unusual combination of multiple endocrine neoplasia (MEN1) and the McCune-Albright syndrome for MEN1 mutations and activating GNAS1 mutations at codons Arg201 and Gln227. METHODS: DNA sequences analyses were performed of the MEN1 gene and codons Arg201 and Gln227 of the GNAS1 gene, using leucocyte and endocrine tissue DNA. RESULTS: A c-->g transversion at position -9 bp in intron 9 of the MEN1 gene was identified. This resulted in the generation of a BmrI restriction endonuclease site, and its presence and segregation with MEN1 in the family was demonstrated by restriction endonuclease analysis. The c-->g transversion was shown to result in the generation of a novel acceptor splice site (ccag) using reverse transcriptase-polymerase chain reaction (RT-PCR) and ribonucleic acid (RNA) obtained from Epstein-Barr virus (EBV)-transformed lymphoblasts. Utilization of this splice site resulted in an abnormal messenger RNA (mRNA) transcript that contained an additional eight bases. This predicted a frameshift that would result in nine missense amino acids followed by a premature termination signal. GNAS1 mutations were not detected in the patient with McCune-Albright syndrome. CONCLUSIONS: The occurrence of MEN1 and the McCune-Albright syndrome in this family are coincidental findings and not due to a common genetic aetiology. However, our results have identified a novel MEN1 mutation that occurs in intron 9 and generates a novel acceptor splice site. Such splicing-affecting genomic variants (SpaGVs) are increasingly being recognized as a cause of human disease, and are likely to be of significance in the 10% of MEN1 patients who do not have coding region mutations.